P-010 Selective posterior cerebral artery amobarbital test: a predictor of memory following subtemporal selective amygdalohippocampectomy. (22nd July 2019) - Catapano, J; Whiting, A; Wang, D; Labib, M; Fredrickson, V; Smith, K; Ducruet, A; Albuquerque, F
Abstract : Introduction: Selective Posterior Cerebral Artery Amobarbital Test (PCA WADA) has been used to predict post-operative memory impairment following temporal epilepsy surgery in patients that have previously failed a traditional intracarotid artery amobarbital test (ICA WADA). Methods: We retrospectively reviewed medical records from 2012 to 2018 for all patients with seizures who underwent selective PCA WADA at our institution, following either failed or inconclusive ICA WADA. Standardized neuropsychological testing was performed prior and during the WADA procedure, as well as post-surgery in patients who underwent resection. Results: A total of 33 patients underwent a selective PCA WADA, with no complications recorded. 26 patients with medically-refractory epilepsy were determined to have a seizure focus amendable to selective amygdalohippocampectomy following extensive EEG monitoring. Of these 26 patients, 6 (23%) patients had a failed PCA WADA and did not undergo selective amygdalohippocampectomy. Another 7 patients (27%) declined surgical resection, leaving 13 patients who underwent subtemporal selective amygdalohippocampectomy. Hippocampal sclerosis was found in all 13 patients (100%) upon pathological examinations. 12 patients (92%) subsequently had formal neuropsychological testing and all were found to have stable memory relative to preoperative examination. 10 patients (77%) were seizure free and had an Engle Grade of I with average follow up of 13 months. Conclusion: Selective PCA WADA is predictive of memory outcomes following a subtemporal selective amygdalohippocampectomy in patients with either a failed or inconclusive ICA WADA. Furthermore, given the low risk of complication and great potential benefit of seizure freedom, A selective PCA Wada may be warranted in medically intractable epilepsy patients that are candidates for a selective amygdalohippocampectomy with a prior failed or inconclusive ICA WADA. Disclosures: J. Catapano: None. A. Whiting: None. D. Wang: None. M. Labib: None. V. Fredrickson: None. K. Smith: None. A. Ducruet: None. F. Albuquerque: None.